2018
DOI: 10.1002/jgm.3013
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for Glut1‐deficient mouse using an adeno‐associated virus vector with the human intrinsic GLUT1 promoter

Abstract: Exogenous GLUT1 expression after AAV-GLUT1 injection approximated that of physiological human GLUT1 expression. Local central nervous system administration of AAV-GLUT1 improved CSF glucose levels and motor function of GLUT1-deficient mice and minimized off-target effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…GLUT1 is largely expressed in red blood cells and endothelial cells, including brain microvessels [48,49]. No alterations in GLUT1 immunoreactivity is found in CJD microvessels; reduction of GLUT1 mRNA correlates with decreased GLUT1 immunoreactivity in the neuropil in CJD.…”
Section: Discussionmentioning
confidence: 96%
“…GLUT1 is largely expressed in red blood cells and endothelial cells, including brain microvessels [48,49]. No alterations in GLUT1 immunoreactivity is found in CJD microvessels; reduction of GLUT1 mRNA correlates with decreased GLUT1 immunoreactivity in the neuropil in CJD.…”
Section: Discussionmentioning
confidence: 96%
“…This study also delineates the temporal requirements for the Glut1 protein, critical to implementing future treatments for Glut1 DS and ensuring optimal therapeutic outcomes. Such information is especially pertinent considering the results of pre-clinical studies that raise the prospect of gene replacement as a means of treating the human condition (12,36). Consistent with the pediatric nature of Glut1 DS and reminiscent of the outcome of similar studies (37, 38) on another infantile-onset disease, spinal muscular atrophy, the earlier we effected Glut1 haploinsufficiency in our conditional mutants, the more closely we were able to mimic disease in constitutively haploinsufficient mutants and in human patients.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches to restore Glut1 protein content and function include upregulation of the normal SLC2A1 allele using small molecule strategies or gene transfer strategies whereby a normal SLC2A1 gene is delivered in a suitable viral vector to the Glut1‐deficient patient 82 . Preclinical experiments in Glut1DS model mice using AAV9 vectors have demonstrated that gene replacement is effective and durable: Brain Glut1 expression and CSF glucose concentrations increase, brain growth and volume are maintained during development, motor performance is preserved, seizure activity is controlled, and brain angiogenesis proceeds normally 82,95,96 . In contrast to successful presymptomatic or early symptomatic treatment, gene replacement in adult mice failed to improve symptoms, suggesting a therapeutic window of opportunity.…”
Section: State Of the Art In Glut1ds And Consensus Recommendationsmentioning
confidence: 99%